Scleral cross section area and volume and axial length - Jonas, Jost B.; Holbach, Leonard; Panda-Jonas, Songhomitra (PLoS ONE, 2014)
To examine whether the scleral cross sectional area and estimated scleral volume are associated with a longer axial length in human eyes.Histologic anterior-posterior sections running through the pupil and the optic nerve head were examined. Using a light microscope, we measured the thickness of the sclera at the limbus, ora serrata, equator, midpoint between equator and posterior pole (MPEPP), peripapillary region and posterior pole. Additionally we determined the length and the cross section area of the sclera.The histomorphometric study included 214 human globes of 214 subjects (mean age: 62.5±13.9 years) (147 eyes enucleated due to malignant choroidal melanoma or due to other non-glaucomatous reasons; 67 eyes enucleated due to secondary angle-closure glaucoma). Mean axial length was 25.1±1.8 mm (median: 24.0 mm; range: 20-35 mm). Scleral thickness measurements decreased with increasing axial length for values taken at the equator (P = 0.008; correlation coefficient r = -0.18), MPEPP (P<0.001;r:-0.47), optic nerve head border (P<0.001;r = -0.47) and posterior pole (P<0.001;r = -0.54). Scleral cross section area decreased significantly with increasing axial lengths for the regions at or behind the equator (P = 0.002;r = -0.21), at or behind the MPEPP (P = 0.001;r = -0.25), and at or behind the optic nerve head border (P = 0.001;r = -0.24). Scleral volume measurements were not significantly associated with axial length.Despite an associated increase in surface area, eyes with longer axial length do not have an increase in scleral volume. It may point against a scleral volume enlargement to play a role in the process of axial elongation.
EVALuna2:21190